Predictors of occupational exposure to styrene and styrene-7, 8-oxide in the reinforced plastics industry. Issue 10 (6th June 2006) - Serdar, B; Tornero-Velez, R; Echeverria, D; Nylander-French, L A; Kupper, L L; Rappaport, S M
Abstract : Objective: To identify demographic and work related factors that predict blood levels of styrene and styrene-7, 8-oxide (SO) in the fibreglass reinforced plastics (FRP) industry. Methods: Personal breathing-zone air samples and whole blood samples were collected repeatedly from 328 reinforced plastics workers in the Unuted States between 1996 and 1999. Styrene and its major metabolite SO were measured in these samples. Multivariable linear regression analyses were applied to the subject-specific levels to explain the variation in exposure and biomarker levels. Results: Exposure levels of styrene were approximately 500-fold higher than those of SO. Exposure levels of styrene and SO varied greatly among the types of products manufactured, with an 11-fold range of median air levels among categories for styrene and a 23-fold range for SO. Even after stratification by job title, median exposures of styrene and SO among laminators varied 14- and 31-fold across product categories. Furthermore, the relative proportions of exposures to styrene and SO varied among product categories. Multivariable regression analyses explained 70% and 63% of the variation in air levels of styrene and SO, respectively, and 72% and 34% of the variation in blood levels of styrene and SO, respectively. Overall, air levels of styrene and SO appear to have decreased substantially in this industry over the last 10–20 years in the US and were greatest among workers with the least seniority. Conclusions: As levels of styrene and SO in air and blood varied among product categories in the FRP industry, use of job title as a surrogate for exposure can introduce unpredictable measurement errors and can confound the relation between exposure and health outcomes in epidemiology studies. Also, inverse relations between the intensity of exposure to styrene and SO and years on the job suggest that younger workers with little seniority are typically exposed to higher levels of styrene and SO than their coworkers.